2022
DOI: 10.17582/journal.pjar/2022/35.1.58.69
|View full text |Cite
|
Sign up to set email alerts
|

Broad Leaved Weed’s Seed Bank and Flora Dynamics in Wheat as Affected by Different Herbicides

Abstract: | To research out an efficient chemical remedy of broad-leaved weeds in winter wheat at Pothwar Region of Pakistan, a study was performed during 2016-17 at University Research Farm Chakwal Road Rawalpindi. Four herbicides were used as once and twice application, i.e., Buctril Super (Bromoxinil 30% with MCPA 30% w/v), Ally Max (Metsulfuron Methyl 14.3% w/w with Tribenuron Methyl 14.3% w/w), Starane M (Fluroxypyre 10% with MCPA 40% w/w) and Clean wave (Aminopyralid 1% with Fluroxypyre14% w/w) at recommended dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…It was also noticed that the number of tillers were increased up to 90th day of crop growth and thereafter, it decreased slightly, which might be due to the not bearing ability of their panicles. Similar results have also been reported by Ali et al [15,19,20,18].…”
Section: Number Of Tillers (M -2 )supporting
confidence: 91%
See 2 more Smart Citations
“…It was also noticed that the number of tillers were increased up to 90th day of crop growth and thereafter, it decreased slightly, which might be due to the not bearing ability of their panicles. Similar results have also been reported by Ali et al [15,19,20,18].…”
Section: Number Of Tillers (M -2 )supporting
confidence: 91%
“…It is also appeared worthy that the treatments like weed free and hand weeding were not found to be economical in comparison to the organic as well as inorganic weed management practices because of high expenditure involved in keeping the plots free of weeds and in hand weeding. the organic and inorganic weed management practices, the better net return and return per rupee investment was mainly due to less increase in cost of cultivation as compared to weed free and hand weeding [15,21] also reported similar results. Further, mulching soil with straw and plastic film can sustain wheat yield and profitability [3,22].…”
Section: Economicsmentioning
confidence: 78%
See 1 more Smart Citation
“…The plants were smaller in size when exposed to these two herbicides as compared to any other herbicide. Along with their impact on overall growth, these were also reported to induce oxidative stress in crop plants (Ali et al, 2004). As a consequence of these chemical herbicides a reduction in nodulation was also seen when specific doses of isoproturon, atrazine and metribuzin in green gram was applied.…”
Section: Herbicidal Weed Managementmentioning
confidence: 99%
“…The findings of L. Butkeviciene et al (2021) experimentally confirmed that in the context of climate change and intensive agriculture, long-term crop rotations increase crop productivity, reduce weeds and the weed seed bank in the soil, and thus contribute to maintaining the resilience of the agroecosystem. The initial field studies by S. Ali et al (2022) on the effectiveness of weed control showed that one of the ways to improve the protective functions of grain-growing technology is the double use of herbicides. Thus, the authors believe, on a reliable scientific basis, that double treatment of wheat crops is accompanied by a 73% increase in grain yield, as well as a significant clearing of crops from weed seeds in the soil.…”
Section: Introductionmentioning
confidence: 99%